The choice of an antibacterial drug for urinary infections treatment in children - A.Ye. Abaturov; A.А. Nikulinа (Zaslavsky O.Yu., 2019)
Infections of the urinary system in childhood take the second place in the frequency of visits for primary medical care. Escherichia coli is the most causative agent of community-acquired forms of infections of the urinary system, which, as a rule, are uncomplicated and are more often diagnosed in girls after three months of age. Klebsiella pneumoniae prevails in nosocomial forms of urinary tract infections, characterized by a complicated course and more often diagnosed in boys up to three months of age. One of the causes of repeated episodes of urinary tract infections is the formation of antibiotic resistance due to the action of β-lactamases of microorganisms on the most commonly used antibacterial drugs of the aminopenicillin group. The literature review substantiates the antibiotic choice for the treatment of urinary infections in children, taking into account the clinical efficacy, safety and sensitivity of the main uropathogens. The results of the randomized clinical trials on the efficacy and safety of the use of the third generation cephalosporin - cefixime in children with urinary tract infections are summarized. Particular attention is paid to maintaining bacterial sensitivity at a level of over 90 % to the action of cefixime in Escherichia coli and Klebsiella pneumoniae, and high compliance with the possibility of a single daily oral administration as an independent therapy on an outpatient basis and the possibility of switching from parenteral use of the third generation cephalosporins to a less invasive, especially in children, oral method.